Development of A New Tool to Analyze Injury Risk: Turkish Get Up Injury Risk Tool - Ahmet Bayrak; Özge Çoban; Mustafa Ertuğrul Yaşa; Necmiye Ün Yıldırım (Pamukkale University, 2024)
Injury risk analysis is critical to preventing injuries' physical and psychological impact. The purpose of this study was to develop a new tool to evaluate the risk of injury particular to the Turkish get up (TGU) exercise. According to expert opinions, the Turkish Get Up Injury Risk Tool (TUGIR) is a biomechanical assessment tool developed based on the Turkish Get Up (TGU) movement. It evaluates the alignment and quality of movement during the exercise to assess the risk of injury. The upper and lower quarter Y balance tests (YBTs) and Functional Movement Screening (FMS) were performed to determine construct validity. A total of thirty- three wrestlers performed all the tests. Reliability was assessed by internal consistency determined with Cronbach's alpha coefficients and inter-rater reliability determined with Kendall's coefficient of concordance. The injury risk cut-off value was calculated according to the Angoff method. The internal consistency of the TUGIR was found to be 0.77 and 0.76, respectively, quite reliable for the right and left sides. Kendall's concordance coefficient of the total score was determined to be 0.998 for both sides. The injury risk cut-off value was found to be %72 for the overall TUGIR score. A low to moderate association was observed between TUGIR and YBTs-FMS. The TUGIR is a novel, reliable, and valid tool for assessing injury risk in sports. This tool offers several advantages, including being an easy-to-use, low- cost, and comprehensive method that can reflect sports-specific biomechanical characteristics. This research could lead to the use of this tool to assess the risk of injury in other sports branches.